Experiences with preventing carpal tunnel syndrome in an automotive plant - Žídková, Věra; Nakládalová, Marie; Zapletalová, Jana; Nakládal, Zdeněk; Kollárová, Helena (International journal of occupational medicine and environmental health, 2017)
OBJECTIVES: Carpal tunnel syndrome (CTS) is a common occupational disease. The aim was to assess the effect of preventive measures in automotive assembly workers. MATERIAL AND METHODS: The analysis summarizes data from annual crosssectional studies. The 7-year analysis of data was based on medical records obtained from an occupational physician and inspections carried out at the workplace where targeted preventive measures were introduced, including better ergonomic arrangement of the workplace, technical adjustments facilitating the work, preventive nerve conduction studies (NCS) testing of the median nerve once a year, switching of workers and their targeted rotation within the workplace. The NCS testing of median nerve conduction at the wrist was the basic objective method for assessment of the prevalence and severity of CTS. Over the study period, the sample comprised 1804 workers at risk for repetitive overuse of the upper extremities, of whom 281 were females with a mean age of 38.5 years and 1523 were males with a mean age of 31.4 years. RESULTS: Over the study period, a total of 13 cases of CTS were recognized as an occupational disease in the plant, 8 of which occurred within the first 2 years from the initiation of production. Introduction of preventive measures decreased the prevalence of median neuropathy from 18.3% of examined extremities in 2011 to 10.5% in 2013 (p = 0.003). In early 2014, the production pace increased and this was accompanied by a rise in abnormal NCS findings to 16.9%. Over the study period, the rate of sensorimotor neuropathy decreased in favor of merely sensory neuropathies, which have been most frequent since 2013. The percentage of employees whose contracts were terminated due to median neuropathy decreased steadily from 5.5% to 0.4%. CONCLUSIONS: Targeted prevention of work-related CTS is effective as evidenced by the decrease in the prevalence of median neuropathy detected by NCS. Int J Occup Med Environ Health 2017;30(1):45-54.
Keywords: occupational diseases; zápěstí; ergonomie; Automobiles; Česká republika; Carpal Tunnel Syndrome; Occupational Diseases; Adolescent; lidé středního věku; nerve conduction studies; lidé; Adult; Czech Republic; Middle Aged; dospělí; nervové vedení; Female; syndrom karpálního tunelu; Median Nerve; Wrist; carpal tunnel syndrome; repetitive overuse; poranění z opakovaného přetěžování; Male; Neural Conduction; ženské pohlaví; prevention; Humans; mužské pohlaví; risk factors; nervus medianus; prevalence; nemoci z povolání; Ergonomics; Cumulative Trauma Disorders; Prevalence; automobily; mladiství